The student's perception on science of qur'an course: A comparative study between islamic public universities - Ibrahim M.A.; Yusoff Z.M.; Yusoff A.M.; Alhamidy A.Q.U.; Shaker M.H.; Sulaiman S.; Razli N.S. (Medwell Journals, 2024)
Indexed by SCOPUS